Physiological and Immunological Study for the Effects of Onopordum Acanthium L. Seeds Oil in Male Rats Treated with CCL4 - Mhammad, Husni Abdulla; Najeeb, Malika Kassim; Jubrail, Amad M. Saleh (Iraqi Journal of Science, 2022)
In this study, the attention was focused on the protective role of seeds oil from local Onopordum acanthium L. (cotton thistle) against tissues damage in the liver, kidney and spleen in male albino rats. Forty adult male rats were randomly divided into four equal groups including control group, rats were treated orally with seeds oil (0.5ml/kg), carbon tetrachloride (CCL4) injected group, and last group was intoxicated with CCL4 and daily treated with seed oil (0.5ml/kg). After four weeks of the experiment, rats were anaesthetized and blood was taken directly by cardiac puncture for the evaluation of studied parameters. Samples of liver, kidneys and spleen were fixed in 10% formalin for histological studies.      From the obtained results, no significant changes were seen in the estimated parameters in the group treated with oil only. In the group injected with CCL4 and treated with oil extract, the level of serum lipids, liver enzymes, total serum bilirubin (TSB), tumor necrosis factor-alpha (TNF-α), C-reactive protein (CRP) and white blood cells (WBCs) were significantly reduced in comparison with untreated CCL4 intoxicated group. The toxicity of CCL4 on the level of fasting blood sugar (FBS), angiotensin-converting enzyme (ACE), high-density lipoprotein (HDL), renal function parameters, hemoglobin and body weight were ameliorated with seeds oil. These effective roles were further supported by the histopathological improvement of the liver, kidney and spleen tissues of rats against CCl4. Conclusion: from the results of this study, it can be concluded that the extracted oil from local Iraqi Onopordum acanthium L. seeds reduced the tissue damages with an improvement of biochemical, hematological and immunological parameters during the four weeks of the experiment.